Inflation Targeting and its Effects on Macroeconomic Performance - Thorarinn G. Petursson (SUERF - The European Money and Finance Forum, 2005)
An increasing number of countries have adopted inflation targeting since New Zealand first adopted this framework in early 1990. Currently there are 21 countries using inflation targeting in every continent of the world. This paper discusses the characteristics of these countries and how the adoption of inflation targeting has affected their economic performance along several dimensions. The main conclusion is that inflation targeting has largely been a success. The new framework has made central banks, which previously lacked credibility, able to change the way they conduct monetary policy towards what is commonly considered best practice. In many respects they have even been leading in creating a new benchmark for how to formulate monetary policy.
Keywords: E42; E52; E58; 330; Inflation targeting; Monetary policy; Inflationssteuerung; Wirkungsanalyse